Atividade antitumoral (in vitro e in vivo) das fisalinas B e D isoladas da Physalis angulata Lin - Magalhães, Hemerson Iury Ferreira (2005)
The present study describes the phytochemical analysis of the chloroform and ethyl acetate partitions obtained from the ethanol extract of Physalis angulata L. (Solanaceae). The sílica gel chromatography resulted on the separation of 5 whytaesteroids (physalina D, B, F, 5-a-etoxi-6-b-hidroxi-5,6-dihidrophysalin B, E and a semi-synthetic physalin named as 5-a-etóxi-6-b-hidróxi-2,3,5,6-tetrahidrophysalin B). The physalins were evaluated for their cytotoxic potentials on 9 tumor cell lines (CEM, HL-60, PC-3, HCT-8, MDA-MB-231, MDA-MB 435, K-562, MCF-7, B-16), on the embryogenesis of sea-urchin eggs and for its lytic capacity in erythrocytes. Antitumoral activity in vivo was observed on a mouse model inoculated with Sarcoma 180. The physalins showed a promising cytotoxic effect, being physalin D the most active on the cell lines (IC50 < 3,0 mg/mL). The physalins D, B, F, 5-a-etoxi-6-b-hidroxi-5, 6-dihidrophysalin B inhibited the progression of the sea-urchin embryo’s cell cycle within a concentration under 30 µg/mL. On the 1st cleavage and blastulae stages, physalin D showed to be the most active, with the respective IC50 of 4.786 and 5.498 µg/mL. On 3rd cleavage, physalin B presented an IC50 of 5.308 µg/mL. None of the physalins showed any sings of lytic activity in concentrations as high as 200 µg/mL. The study about the physalins effects upon cell viability (trypan blue daye) and death mechanisms on HL-60 cells (EB/AO staining) suggests that physalins B and D were the strongest inducers of apoptosis. Physalin D also induced cellular necrosis on a rather intense level. Physalin B, on doses of 10 and 25 mg/Kg, inhibited tumor growth on 44 e 52%, respectively, while physalin D inhibited tumor growth on 45% in both treatments. The antitumor activity in vivo was related to the lowest proliferation rate, as evaluated by the Ki-67 antibody marker. The histopathological analysis of kidney and liver suggests that those organs are affected, in a reversible manner, on mice treated with physalins.